National evaluation of risk factors for unplanned readmission after lung resection. (26th February 2022) - Pons, Aina; Guirao, Ángela; Fibla, Juan J; Carvajal, Carlos; Embun, Raúl; Sánchez, David; GEVATS,; Hernández, Jorge
Abstract: OBJECTIVES: Unplanned readmission is defined as the return to inpatient hospitalization within 30 days after discharge. Worldwide, its incidence after lung resection ranges between 8% and 50%, and it has been shown to impact both patient recovery and healthcare resources. Our goal was to identify the risk factors to prioritize early follow-ups. METHODS: We analysed data from the database of the Grupo Español de Cirugía Torácica Video-Asistida from 33 thoracic surgery departments over 15 months. Standard tests were used to compare the different risk groups. Our goal was to present the most relevant explanatory variables for readmission. RESULTS: A total of 174 of 2808 patients (6%) underwent unplanned readmission after a lobectomy. Of all the preoperative individual characteristics, only lung function was found to be a risk factor for readmission [forced expiratory volume in 1 s < 80%, risk ratio (RR) 1.78, P < 0.001; diffusing capacity of carbon monoxide <60%, RR 1.6, P = 0.02; and VO2 < 20 ml/kg/min, RR 1.59, P = 0.02]. The tumour's characteristics and the stage of the disease did not have an influence on the readmission rates. In the readmitted cohort, an open approach or thoracotomy was associated with more frequent readmissions (RR 1.77; P < 0.001). Strong adhesions (RR 1.81; P < 0.001) or adhesions occupying more than half of the hemithorax (RR 1.73, P < 0.001) were also found to be risk factors for readmission and for longer operative times. A length of stay of >10 days after a lobectomy was found to be a risk factor for readmission (RR 1.9). CONCLUSIONS: We identified preoperative, intraoperative and postoperative risk factors for readmission. This information can be a useful tool to help with the prioritization of early follow-ups, especially in centres with high workloads.